Protocolos de leitura: uma proposta interdisciplinar - Santos, Wanderléa Oliveira (2007)
The difficulties to work with reading activity in classroom motivated this research about reading, which focuses the reading practice of History teachers. It investigates how historical and social facts are mediated through the text. The aim is to encourage a reading pedagogical practice from the creation of reading protocols, in an interdisciplinary proposal, between the subjects Portuguese Language and History in the primary school. The construction of reading protocols demands a multiple vision about reading, in which the ethic is able to surpass canons and build a critical interpretation. This one submitted to the rhetoric, truth, textuality and reason, contributing to the education of a subject-reader, in a collective work among educators and students